HEALTH PROFESSIONALS TALK MORE ABOUT CARE THAN ABOUT ACQUIRED IMMUNODEFICIENCY SYNDROME - Cleuma Sueli Santos Suto; Sergio Corrêa Marques; Denize Cristina Oliveira; Jeane Freitas de Oliveira; Mirian Santos Paiva (Universidade Federal do Paraná, 2017)
This study aimed to apprehend the social representations elaborated by health professionals on the acquired immunodeficiency syndrome and care to people living with the human immunodeficiency virus through comparison of the diversity and rarity indexes. This is a multi-method study, based on the Theory of Social Representations, involving 73 health professionals, in four specialized services units, in the city of Salvador, Bahia, in 2015. Data was collected with the use of the free word association test (processing was made with EVOC software) and calculation of centrality degrees. 'Prejudice and death "are the nucleus of the representation of the acquired immunodeficiency syndrome, and "advice and care" constitute the nucleus of Care. It is concluded that the structuring elements of social representation denote the presence of value judgments, and the calculation of diversity and rarity indexes revealed that there was less sharing of evocations about the disease than about Care.